Evaluation of residual products from heavy oil refining for the use as an asphalt pavement material. Issue 1 (2nd January 2017) - Shin, O-Cheol; Yang, Sunglin; Im, Jeong Hyuk; Baek, Cheolmin; Rhee, Suk Keun; Hwang, Sung Do
Abstract : Global oil prices are increasing, and the current demand for the fuel is outpacing the supply of traditional crude oil sources. Therefore, the petroleum industry has applied great effort to extract more valuable products such as fuel from heavy oil sources such as Canadian oil sands and Venezuelan heavy oils. One refining process that uses heavy oil sources is the solvent deasphalting (SDA) process. SDA extracts most oil components, leaving residual products with more asphaltenes compared to the conventional asphalt binder for road pavement. In this study, the physical and chemical properties of the residual products, known as pitch, have been investigated to evaluate their applicability as a binder for asphalt pavement. From the various tests, it was found that the pitch is too hard and brittle to be used for asphalt pavement due to its very high viscosity. Therefore, the pitch was modified with vegetable-oil-based additives, after which it exhibited similar basic material properties and rheological behaviours to those of conventional asphalt binder, indicating that the modified pitch could be used as a binder for asphalt pavement.